Relasi Manusia Dan Hukum Lingkungan Human Relations And Environmental Law - Muhammad Ajiseftian Suryatama; Mustar; Surya Sukti (Jurnal Riset Multidisiplin Edukasi, 2025)
Law and humans have a close relationship in creating a social order. As God's created beings, man is made up of a body and a spirit, where the spirit plays a role in shaping moral consciousness as well as legal behavior. In its development, law serves not only as a rule that governs human life, but also as a reflection of social and cultural values. The results of the discussion explained: 1) Human beings consist of bodies and spirits, with spirit as a vital element that forms personality and morality. In philosophy, man has the freedom to develop, but still depends on God. The search for spiritual satisfaction is the main goal of finding the meaning of life. 2) Law has two main forms: descriptive (natural phenomena) and prescriptive (regulating human behavior). The philosophy of law examines the basic nature of law, relates to culture and social values, and has various sources, such as God, reason, and legal consciousness. 3) Philosophy in human relations and environmental law seeks to create a sustainable balance between human needs and the preservation of nature, with the aim of achieving human welfare that does not damage the welfare of other living beings and future generations.